Necessity Analysis 0f Basic Life Support Competency Improvement On The Out Of Hospital Cardiac Arrest Patients For The Employees Of Disaster Prevention And Mitigation Service In Middle Halmahera, North Maluku - Abd Hakim Husen (Institute of Computer Science (IOCS), 2021)
Emergency situation is a sudden incident which require an immediately action. It can be caused by epidemic situation, natural disaster, technology disaster, conflict, or human error. Out-of-hospital cardiac arrest (OHCA) is one of health problem in the world which is caused by the emergency situation. Survival rate of the victims depends on how well trained the medical personnel about basic life support (BLS) while treating OHCA patients. BLS must be given to patient with respiratory failure or cardiac arrest (code blue patients). BLS competency is not exclusive for medical personnel only, but it can be taught to everyone. The purpose of this study was analyzed the necessity of BLS competency improvement on the OHCA patients for the employees of Disaster Prevention and Mitigation Service in Middle Halmahera Regency. This study was a quantitative research with cross sectional study method. The samples were 30 active employees of Disaster Prevention and Mitigation Service in Middle Halmahera Regency. The result showed 43,3% employees had poor BLS competency, only 23,3% employees had a good BLS competency. Chi Square analysis result showed there was a significant correlation (p=0,000) between the necessity of BLS improvement training and BLS competency on the OHCA patients. BLS competency is a basic knowledge for public service employee especially in Disaster Prevention and Mitigation Service. The employees in Disaster Prevention and Mitigation Service in Middle Halmehara Regency had a poor BLS competency, so BLS improvement training is needed.